Clinical Updates on COVID-19 (API-ICP Guidelines on COVID-19) - Arulrhaj, S. (Jaypee Brothers Medical Publishers, 2020)
The aim of this book is to focus on the Clinical Updates on COVID-19 (API-ICP Guidelines on COVID-19). A rapidly evolving pandemic, coronavirus disease 2019 (COVID-19) is a relatively unique infection showing a much greater infectivity, although with a lower severity and case-fatality rate in comparison to severe acute respiratory syndrome (SARS), caused by a homologous virus. The first confirmed case of COVID-19 pandemic was reported in India by end of January 2020. As this disease is very new, physicians are still to learn about its behavior. Thus, the WHO has instructed all information regarding COVID-19 to be open access so that all doctors in the world can access. Association of Physicians of India (API) has also followed the footsteps of the WHO and has rendered itself in committing itself for the upgradation and integration of knowledge among the nation. This book consists of 14 chapters, which include epidemiology of COVID-19, virology and pathophysiology of COVID-19, clinical features of COVID-19, diagnosis of COVID-19, management of COVID-19, API-ICP guidelines for ICU support in COVID-19 infection, API guidelines for gastroenterology practice in the COVID-19 scenario, COVID-19 and the kidney, COVID-19 and geriatrics, and hematological clues to COVID-19 infection. This book becomes the much-needed beacon of light to the physicians who have been serving during this moment of absolute crisis in trying to save the lives of the infected.